'Should I stay or should I go?': unpacking teacher attrition/retention as an educational issue. Issue 8 (17th November 2017) - Kelchtermans, Geert
Abstract: The paper starts from the observation that teacher attrition/retention seems to be a wicked issue: it seems to have strong face validity and a commonsense meaning, but the literature doesn't provide a clear and distinctive definition. In the first section, the author analyzes the different ways in which the issue of teacher attrition and retention is problematized—in general and educationally—as the basis for a definition: as an educational issue, teacher attrition and retention refers to the need to prevent good teachers from leaving the job for the wrong reasons. Arguing that teacher attrition/retention constitutes both a problem and a challenge, he continues in the second part of the article foregrounding several lessons learned from the research on teacher attrition. A first lesson is related to the central role of social relationships and teachers' need for social recognition as well as sense of belonging. Secondly, the impact of performativity policies on teacher attrition is discussed. A final lesson looks at teacher attrition and retention from the perspective of career and teachers' work lives. The conclusion section outlines an agenda for teacher education, teacher induction, and school development to positively deal with the challenge to keep the good teachers in teaching.